XML Certification Quizzer. - Amoussou, Joel (XML journal :the ultimate enterprise resource.)
This column has two objectives. The first is to help you prepare for IBM Test 141 on XML and related technologies. The second is to help you learn XML by offering tips for designing and optimizing XML solutions.